KARAKTERISTIK KUE PUKIS DARI PERBANDINGAN MODIFIED CASSAVA FLOUR (MOCAF) DAN PASTA LABU KUNING (Cucurbita moschata Durch) - Purnamasari, Ni Kadek Maya; Ina, Putu Timur; Wiadnyani, A.A.I. Sri (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 7 No 3 (2018): Jurnal ITEPA, 2018)
The purposes of this research were to know the effect of mocaf and pumpkin pasta ratio on the characteristics of pukis and to know the right ratio from mocaf and pumpkin pasta to produce pukis with the best characteristics. The experimental design was used randomized block design with the treatment’s factor is ratio of mocaf with pumpkin pasta that is 90% : 10%; 80% : 20%; 70% : 30%; 60% : 40%; 50% : 50%; dan 40% : 60%. The treatment was repeated as many as 3 repetitions then obtained 18 units. The data obtained were analyzed by variance and if the treatment had an effect on the variable then continued with Duncan test. The results showed that mocaf and pumpkin pasta ratio had significant effect to water content, ash content, total caroten, skoring test (colour, aroma, texture, taste), and hedonic test (colour, aroma, texture, taste, and overall acceptance). Ratio from mocaf and pumpkin pasta (60 % : 40%) is the best characteristic with water content is 57,62%, ash content is 0,84%, total caroten is 2779,97 ?g/g, color orange and liked, flavor typical pumpkin and liked, texture soft and liked, taste rather typical pumpkin and liked and overall acceptance liked.